Development of a Hydrous Ethanol Fuel Feeding Device for Spark-Ignition Engine - Belonio, Alexis T.; Regalado, Manuel Jose C.; Tado, Neil Caesar M.; Sicat, Emmanuel V. (Journal of Technology Innovations in Renewable Energy, 2014)
While the Philippine Biofuels Act of 2006 mandates the use of anhydrous bioethanol as blend for gasoline, the potential of hydrous ethanol as an alternative fuel for spark-ignition engines has not been fully realized. This study explored the possibility of using hydrous ethanol as fuel for spark-ignition engines with minimal modifications and without the need for gasoline blend. A fuel feeding device was developed to feed hydrous ethanol fuel into the intake manifold of the engine, bypassing the carburetor. By replacing the components that are not compatible with hydrous ethanol and installing a fuel feeding device developed at PhilRice, two spark-ignition engines were able to run solely on 80-95% hydrous ethanol fuel. The fuel economy was found to be a significant issue in the utilization of hydrous ethanol fuel as there is a 75% increase in fuel consumption when using hydrous ethanol. There is potential for hydrous ethanol to be used as fuel if it can be produced locally and sold at half the pump price of gasoline.